Acute renal impairment characterization using diffusion magnetic resonance imaging: Validation by histology. (10th July 2019) - Yu, Zhixian; Zhu, Honghui; Wu, Xiuling; Chen, Zhongwei; Zhang, Zhao; Li, Jiance; Ye, Qiong
Abstract : Diffusion magnetic resonance imaging has been demonstrated to be a simple, noninvasive and accurate method for the detection of renal microstructure and microcirculation, which are closely linked to renal function. Moreover, serum endothelin‐1 (ET‐1) was also reported as a good indicator of early renal injury. The aim of this study was to evaluate the feasibility and capability of diffusion MRI and ET‐1 to detect acute kidney injury by an operation simulating high‐pressure renal pelvic perfusion, which is commonly used during ureteroscopic lithotripsy. Histological findings were used as a reference. Fourteen New Zealand rabbits in an experimental group and 14 in a control group were used in this study. Diffusion tensor imaging and intravoxel incoherent motion diffusion‐weighted imaging were acquired by a 3.0 T MRI scanner. Significant corticomedullary differences were found in the values of the apparent diffusion coefficient (ADC), pure tissue diffusion, volume fraction of pseudo‐diffusion (fp) and fractional anisotropy (FA) ( P  < 0.05 for all) in both preoperation and postoperation experimental groups. Compared with the control group, the values of cortical fpmean, medullary ADCmean and FAmean decreased significantly ( P  < 0.05) after the operation in the experimental group. Also, the change rate of medullary ADCmean in the experimental group was more pronounced than that in the control group ( P  = 0.018). No significant change was found in serum ET‐1 concentration after surgery in either the experimental ( P  = 0.80) or control ( P  = 0.17) groups. In the experimental group, histological changes were observed in the medulla, while no visible change was found in the cortex. This study demonstrated the feasibility of diffusion MRI to detect the changes of renal microstructure and microcirculation in acute kidney injury, with the potential to evaluate renal function. Moreover, the sensitivity of diffusion MRI to acute kidney injury appears to be superior to that of serum ET‐1. Abstract : Diffusion MRI can accurately and rapidly detect pathological alterations in acute kidney injury, which is consistent with pathological findings. Moreover, its sensitivity appears to be superior to that of serum endothelin‐1 (ET‐1).